A high-protein diet containing inulin/oligofructose supports body weight gain associated with lower energy expenditure and carbohydrate oxidation, and alters faecal microbiota in C57BL/6 mice. (13th July 2021) - Koch, Franziska; Derno, Michael; Langhammer, Martina; Tuchscherer, Armin; Hammon, Harald M.; Mielenz, Manfred; Metges, Cornelia C.; Kuhla, Björn
Abstract: Prebiotic supplements and high-protein (HP) diets reduce body weight and modulate intestinal microbiota. Our aim was to elucidate the combined effect of an inulin/oligofructose (FOS) and HP diet on body weight gain, energy metabolism and faecal microbiota. Forty male C57BL/6NCrl mice were fed a control (C) diet for 2 weeks and allocated to a C or HP (40 % protein) diet including no or 10 % inulin/FOS (C + I and HP + I) for 4 weeks. Inulin/FOS was added in place of starch and cellulose. Body weight, food intake, faecal energy and nitrogen were determined. Indirect calorimetry and faecal microbiota analysis were performed after 3 weeks on diets. Body weight gain of HP-fed mice was 36 % lower than HP + I- and C-fed mice ( P < 0⋅05). Diet digestibility and food conversion efficiency were higher in HP + I- than HP-fed mice ( P < 0⋅01), while food intake was comparable between groups. Total energy expenditure (heat production) was 25 % lower in HP + I- than in C-, HP- and C + I-fed mice ( P < 0⋅001). Carbohydrate oxidation tended to be 24 % higher in HP- than in HP + I-fed mice ( P < 0⋅05). Faecal nitrogen excretion was 31–45 % lower in C-, C + I- and HP + I- than in HP-fed mice ( P < 0⋅05). Faecal Bacteroides–Prevotella DNA was 2⋅3-fold higher in C + I- and HP + I- relative to C-fed mice ( P < 0⋅05), but Clostridium leptum DNA abundances was 79 % lower in HP + I- than in HP-fed mice ( P < 0⋅05). We suggest that the higher conversion efficiency of dietary energy of HP + I but not C + I-fed mice is caused by higher digestibility and lower heat production, resulting in increased body mass.